1998
DOI: 10.1159/000016459
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Distribution in Sound and Carious Root Tissues of Human Teeth

Abstract: Proton probe analysis has been used to provide for the first time quantitative F concentration data in carious root tissues from subjects consuming water containing 1 ppm F. In small lesions at the neck of the tooth with minimal tissue loss the F concentration was significantly higher at the outer lesion edge than at the outer edge of adjacent sound root tissue. In one sample with high F values the lesion edge had 19,000 ppm F and the adjacent sound root surface 5,400 ppm F (μg F/g apatite). In large lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Residents in the unfluoridated area presented 21% more root caries per person than those with root caries from the fluoridated area. A proton probe was employed to provide a quantitative estimation of fluoride concentration in carious root tissues from subjects consuming water containing 1 ppm fluoride [Shu et al, 1998]. They reported that in large lesions with extensive cavitation fluoride was concentrated in the outer edge of the lesion and was significantly higher (1,800-4,100 ppm) than in adjacent sound inner dentine (190-290 ppm).…”
Section: Use Of Dentifrices Containing Fluoride For the Management Ofmentioning
confidence: 99%
“…Residents in the unfluoridated area presented 21% more root caries per person than those with root caries from the fluoridated area. A proton probe was employed to provide a quantitative estimation of fluoride concentration in carious root tissues from subjects consuming water containing 1 ppm fluoride [Shu et al, 1998]. They reported that in large lesions with extensive cavitation fluoride was concentrated in the outer edge of the lesion and was significantly higher (1,800-4,100 ppm) than in adjacent sound inner dentine (190-290 ppm).…”
Section: Use Of Dentifrices Containing Fluoride For the Management Ofmentioning
confidence: 99%
“…Fluoride incorporation into tooth mineral may result also in reduced demineralization since fluoroapatite is somewhat less acid‐soluble than is hydroxylapatite. However, it is well know that the fluoride important for caries reduction is that in plaque, although it appears that fluoride from dissolved enamel or from fluoride‐containing varnishes may enter into plaque and become part of the total [97,100]. Moreover, this released fluoride can inhibit acid production by plaque bacteria [44].…”
Section: Introductionmentioning
confidence: 99%
“…6 Fluoride-and CHX-containing antibacterial agents can be promising for the remineralization of initial root caries. However, such varnishes can penetrate demineralized root dentin only up to 40% of the total lesion depth, due to their hydrophobic nature.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Fluoride inhibits root caries, as it does coronal caries, even though the tissues initially affected are quite different. 6 Several in situ and in vivo studies demonstrated the cariostatic effect of topically applied fluorides on initial root surface lesions. [7][8] Chlorhexidine (CHX)-containing products are noteworthy, because of their ability to reduce pathogens from the immediate environment and possibly from carious dentin and soft tissues.…”
Section: Introductionmentioning
confidence: 99%